Transitory market reforms: mechanisms and effects over firms’ performance - Barros, Octavio Augusto Darcie de (2018)
We improve upon existing literature on institutional reforms by analyzing a different type of reform that is very common in Latin American countries: the transitory market reforms. Under transitory market reforms, uncertainty lasts longer due to the more frequent shifts between opposing market orientations, thus reducing firms’ capacity to estimate their risk. We hypothesize that transitory reforms have a negative effect over firms’ profitability, and that this relationship is negatively moderated by institutional convergence, in which market agents have already comprehended the new institutional rules but are still internalizing them in their strategies. We test these relationships in a sample of 22,066 observations from 1,005 Brazilian firms and find support to our hypotheses. Reforms mechanisms are further analyzed and discussed, as well as their implications for theory.